Histological comparison of Platelet rich fibrin clots prepared by fixed-angle versus horizontal centrifugation. (3rd April 2021) - Fujioka-Kobayashi, Masako; Kono, Michihide; Katagiri, Hiroki; Schaller, Benoit; Zhang, Yufeng; Sculean, Anton; Miron, Richard J.
Abstract: Platelet-rich fibrin (PRF) is prepared from whole blood without any exogenous coagulation factors. Several preparation methods have now been introduced, particularly with differences in centrifugation parameters including g-force and time to improve their regenerative potential. Nevertheless, the centrifugation systems have not yet been clearly investigated for their influences on the PRF clot properties. The aim of the present study was to visually and histologically characterize the cell separation manner and blood cell localization on the whole PRF clots prepared by two different centrifugation system, fixed-angle and horizontal centrifugation. Leukocyte- and platelet-rich fibrin (L-PRF) was prepared on a fixed-angle centrifuge machine (IntraSpin, Intra-Lock, FL, USA) at 2700 rpm ( 400 g at the RCF-clot; 700 g at the RCF-max) for 12 min. The PRF prepared by horizontal centrifugation was prepared on a horizontal centrifugation (H-PRF) (Eppendorf 5702, Eppendorf, Germany) at 700 g at the RCF-max for 8 min. The cell morphology and localization were observed on the surface of PRF clots by scanning electron microscopy (SEM) and histologically by transaxial frozen sections by means of a film method. L-PRF clots demonstrated a sloped separation between the upper plasma and the bottom red blood cell (RBC) layers according to the angle of the rotor. Red dots were often observed on the distal walls of the tubes in the upper layers, consisting of aggregations of RBCs, leukocytes and platelets by SEM and histology. Clots produced on the horizontal centrifuge showed much smoother cell layer distribution/separation along the tube surfaces when compared to L-PRF. Horizontal centrifugation also demonstrated more evenly distributed platelets throughout the PRF clots when compared to L-PRF that gathered the majority of cells along the distal tube surface or within the buffy-coat region. In summary, it was found that horizontal centrifugation resulted in a more uniform blood cell separation of PRF clots when compared to the accumulation of cells gathered along the distal tube surfaces produced prepared by fixed-angle centrifugation. Future research is needed to evaluate the benefit of horizontal centrifugation in clinical practice.